A NEW BACULOVIRUS ISOLATE THAT DOES NOT CAUSE THE LIQUEFACTION OF THE INTEGUMENT IN Spodoptera frugiperda LIQUEFACTION OF THE INTEGUMENT IN Spodoptera frugiperda DEAD LARVAE - VALICENTE, FERNANDO HERCOS; TUELHER, EDMAR DE SOUZA; PAIVA, CARLOS EDUARDO COSTA; GUIMARÃES, MARIA RAQUEL FELLET; MACEDO, CORINA VIEIRA; WOLFF, JOSÉ LUIS CALDAS (International Journal of Maize & Sorghum, 2010)
The large-scale production of Baculovirus to control fall armyworm, Spodoptera frugiperda, presents many limitations. The most important limiting factor is that the baculovirus, which infects fall armyworm, causes liquefaction of the integument immediately after death. This disruption of the integument difficultates the large scale production because dead insect must be frozen before being harvested. This fact implies in high lab work need, increasing the cost of the biopesticide. This problem was overcome by the discovery of a new baculovirus nucleopolyhedrovirus (NPV) isolate in Cascavel/PR, that doesn’t cause liquefaction of the integument (isolate 6NR) immediately after the insect death. This is an extremely important factor in a large-scale baculovirus production. In addition, mortality caused by isolate 6NR on 6-day-old-larvae was above 93% (SEM=0.7%), the average weight dead larva was 116.21 mg (SEM=22.9), the larval equivalent and weight equivalent/ha were 15.04 g (SEM=1.2) and 140.32 larvae (SEM=20.1), respectively.